Growth factor activation of an amiloride-sensitive Na+/H+ exchange system in quiescent fibroblasts: coupling to ribosomal protein S6 phosphorylation. - Pouysségur, J (1982)
Chinese hamster lung fibroblast cells (CCl39) enter the G0/G1 nonproliferative state after serum deprivation. In this report, we show that reinitiation of DNA synthesis by serum or the combination of purified human thrombin and insulin (1-10 microgram/ml) is preceded by very early stimulation of ionic fluxes (Na+/Rb+) and protein phosphorylation (27,000 daltons, 62,000 daltons, and the ribosomal S6 proteins). The potentiating action of insulin on thrombin-stimulated DNA synthesis is also observed on thrombin-stimulated Na+ influx, Rb+ influx, and protein S6 phosphorylation. Moreover, we demonstrate that CCl39 cells possess a Na+/H+ exchange system sensitive to amiloride. Half-maximal inhibition of growth factor-activated Na+ influx and Na+-dependent H+ efflux is obtained with 3-10 microM amiloride. Two lines of evidence indicate that the extrusion of H+ via the activation of the Na+/H+ exchanger is coupled to protein S6 phosphorylation: serum-stimulated phosphorylation is blocked by (i) amiloride at a concentration that abolishes serum-stimulated Na+ influx and (ii) protonophores that acidify the cell interior. The present data support the idea that the regulation of intracellular pH is a key event in the mechanism of growth factor action.